Pathways to Sustainable Mobility at Universities - a Case Study at the Environmental Campus Birkenfeld - Klaus Helling; Dorit Schumann Bölsche (Journal of Sustainability Perspectives, 2023)
More and more universities are recognizing their role model and creative function in society and are acting accordingly - also in terms of mobility. In this way, universities can make an important contribution to climate protection, as mobility is responsible for more than 20 percent of global greenhouse gas emissions. The GreenMetric ranking also takes the area of mobility into account via the Transportation category, which is weighted at 18%. This paper uses the example of the Environmental Campus Birkenfeld at Trier University of Applied Sciences, Germany, to show what opportunities universities in rural areas have to reduce transportation-related emissions of students and employees. The possibilities of avoiding transportation as well as different solutions for the reduction of transportation-related greenhouse gas emissions are discussed. Furthermore, conflicts of objectives inherent to the university system in the area of mobility are considered, especially in the area of internationalization.